Psychological Factors Influence EFL Students’ Interest - Yolanda Resta Clasa Kanter (Borneo Educational Journal (Borju), 2019)
The subject of this research was the students of SMP Negeri 34 Samarinda, and the object was this research was the factors that influence students’ interest in learning English. The population and sample of this research were all of the students in class VIII at SMP N 34 Samarinda. They consisted of eight D classes. The total were number of the population was 27 students. The technique used in collecting data was questionnaire. To analyze the data, the researcher used descriptive statistic to analyze the data. The researcher used mean to known the score. Based on the data analysis, it can be seen that the factor that influence of students’ interest is categorized into middle (63%). There are some factors that influence students’ interest in learning English. They are: internal factors (come from the students themselves such as attention, intelligence, and readiness) and external factors such us parent and teacher. The dominant factors that influence students interest is external factors from the teacher factor